The adventures of Miranda in the brave new world: learning in a Web 2.0 millennium - Cameron Barnes; Belinda Tynan (Association for Learning Technology, 2007)
This paper looks at the implications of Web 2.0 technologies for university teaching and learning. The latest generation of undergraduates already live in a Web 2.0 world. They have new service expectations and are increasingly dissatisfied with teacher-centred pedagogies. To attract and retain these students, universities will need to rethink their operations. New social technologies mean that universities have the chance to create a new generation of student-centred learning environments, to realize the idea of a University 2.0. The following discussion draws upon a fictional character in order to capture the possible futures of such a brave new world.